Recurrent assessment of lymphocyte subsets in 32 patients with multisystem inflammatory syndrome in children (MIS‐C) - Okarska‐Napierała, Magdalena; Mańdziuk, Joanna; Feleszko, Wojciech; Stelmaszczyk‐Emmel, Anna; Panczyk, Mariusz; Demkow, Urszula; Kuchar, Ernest; Riggioni, Carmen (Pediatric allergy and immunology, 2021)
Background Lymphopenia is a hallmark of multisystem inflammatory syndrome in children (MIS‐C). We aimed to characterize lymphocyte subsets' shifts and their correlations with other severity markers of MIS‐C. Methods In this prospective cross‐sectional study, we performed peripheral lymphocyte phenotyping in 32 patients with MIS‐C. We analyzed lymphocyte subsets at three time points of the disease: the acute (A), convalescent (B), and recovery (C) phases. Based on age‐normalized lymphocyte counts, we distinguished two groups of patients: “the mild” (higher lymphocyte counts) and “the severe” (lower lymphocyte counts). In addition, we examined differences between these groups regarding other severity markers. Results In phase A, 84% of children had lymphopenia. Decreased absolute counts of CD3, CD4, and CD8 cells were observed in, respectively, 88%, 72%, and 84% of patients. The natural killer cells were decreased in 63% and CD19 in 59% of children. “The severe” group had significantly higher procalcitonin and troponin I levels and lower platelets and albumin. Moreover, “the severe” group had hypotension more frequently (73% vs. 20%, p = .008). In phase B, all lymphocyte counts increased, and 32% of children had lymphocytosis. The increase of CD3, CD4, and CD8 counts correlated with some laboratory severity markers (hemoglobin, procalcitonin, D‐dimer, lactate dehydrogenase, N‐terminal prohormone of brain natriuretic peptide, albumin), but not with steroid use. In phase C, most children had normal lymphocyte counts. Conclusions Substantial shifts in lymphocyte counts during MIS‐C apply most to T lymphocytes and correlate with the disease severity markers, particularly hypotension prevalence. A proportion of children with MIS‐C develops transient lymphocytosis during convalescence.